2017
DOI: 10.1038/s41598-017-00363-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CA20, a score based on centrosome amplification-associated genes, in breast tumors

Abstract: Centrosome amplification (CA) is a hallmark of cancer, observable in ≥75% of breast tumors. CA drives aggressive cellular phenotypes such as chromosomal instability (CIN) and invasiveness. Thus, assessment of CA may offer insights into the prognosis of breast cancer and identify patients who might benefit from centrosome declustering agents. However, it remains unclear whether CA is correlated with clinical outcomes after adjusting for confounding factors. To gain insights, we developed a signature, “CA20”, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…To estimate relative CA levels in human samples, we used CA20, a score based on the expression of 20 genes experimentally associated with CA [ 23 ], as a surrogate. We quantified CA20 across the transcriptomes (profiled by RNA-seq) of 9,721 tumour and 725 matched-normal samples spanning 32 cancer types from TCGA ( Fig 1a , S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate relative CA levels in human samples, we used CA20, a score based on the expression of 20 genes experimentally associated with CA [ 23 ], as a surrogate. We quantified CA20 across the transcriptomes (profiled by RNA-seq) of 9,721 tumour and 725 matched-normal samples spanning 32 cancer types from TCGA ( Fig 1a , S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is one of the best studied cancer types, with large cohorts of clinically annotated tumour samples available [ 27 , 28 ], and where the CA20 score was developed [ 23 ]. In addition, CA has been frequently correlated with aggressive features in breast cancer [ 6 , 25 , 26 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two scores to determine CA in clinical samples that have previously been reported: the centrosome index (CI) (34,35) and the centrosome amplification 20 (CA20) (36). Both of these scores are calculated from mRNA expression values of certain genes required for centriole duplication.…”
Section: Resultsmentioning
confidence: 99%
“…Ogden et al identified and validated CA20, a 20 gene CA transcriptomic signature (consisting of centrosome structural genes and genes involved in inducing CA), in breast tumors. CA20 is an independent predictor of poor survival and a high score is indicative of high chromosomal instability (CIN) and tumor aggressiveness [148]. Later, Almeida et al in their pan-cancer computational analysis (from The Cancer Genome Atlas [TCGA] cohort) confirmed the association of CA20 with clinical and molecular features of BC as well as with CIN.…”
Section: Scoring Centrosome Amplification: An Emerging Prognosticmentioning
confidence: 99%